INDIVIDUALIZATION OF PROFESSIONALLY ORIENTED EDUCATION AS A BASIS FOR IMPROVING THE EFFICIENCY OF STUDY FOREIGN LANGUAGES IN HIGHER PEDAGOGICAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2011)
The problem of improvement of students' prifessional oriented learning effectiveness at non-linguistics specialities in the Higher Pedagogical School is examined. The authour considers individualization of the professional oriented learning of foreign languages as the basis of the current educational process.
Keywords: individualization; professional oriented; the Higher Pedagogical Schools; the educational process